Effect of P and Ge doping on microstructure of Sn-0.3Ag-0.7Cu/Ni-P solder joints. Issue 4 (5th September 2016) - Yan, Xingchen; Xu, Kexin; Wang, Junjie; Wei, Xicheng; Wang, Wurong
Abstract : Purpose: The purpose of this paper is to comparatively investigate the microstructure and interfacial intermetallic compound (IMC) layer of Cu/SACPG/Ni and Cu/SAC0307/Ni solder joints after thermal aging. Design/methodology/approach: The specimens were thermally aged at 150°C for 0, 24, 168 and 500 h. The microstructure and morphology of the interface IMC layer were observed by means of scanning electron microscope. The IMCs and the solder bump surface were analyzed by EDS. Moreover, the thickness of IMC layer was measured by using the image analysis software. Findings: The morphology of IMC of Cu/SAC0307/Ni solder joint was consistent with that of the Cu/SACPG/Ni joint, which indicates that the addition of P and Ge had little effect on the IMC formation. The needle-like (Cu, Ni)6Sn5 was formed at the interface of solder/Ni solder joints. Meanwhile, the tiny particles inferred as Ag3Sn phase attached to the surface of (Cu, Ni)6Sn5. The growth rate of IMC layer of the Cu/SACPG/Ni joint was smaller than that of Cu/SAC0307/Ni joint with aging time increasing, which means the addition of trace P and Ge can slightly suppress the diffusion rate of the interfacial IMC. Originality/value: There are no previous studies on the formation mechanism of the IMC layer of SAC0307 solder alloys with P and Ge addition.